2017
DOI: 10.1111/jonm.12480
|View full text |Cite
|
Sign up to set email alerts
|

The influence of authentic leadership on safety climate in nursing

Abstract: Exhibiting the characteristics of authentic leadership, or improving them and reflecting them on to personnel can enhance the safety climate. Planning information sharing meetings to raise the personnel's awareness of safety climate and systemic improvements can contribute to creating safe care climates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 45 publications
(57 reference statements)
6
81
1
4
Order By: Relevance
“…For instance, the statement I admit my mistakes to others (item_16), which was originally a part of the relational transparency, was qualified into the moral processing subscale. The above‐mentioned observations support the thesis about the need to develop a model of authentic leadership dedicated to nursing, which would consider rationing nursing care (Fast & Rankin, ) and patient safety (Agnew et al., ; Dirik & Seren Intepeler, ; Perry, ; Stewart & Usher, ). Such a model can be important for in improving the curricula of pre‐ and postgraduate courses.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…For instance, the statement I admit my mistakes to others (item_16), which was originally a part of the relational transparency, was qualified into the moral processing subscale. The above‐mentioned observations support the thesis about the need to develop a model of authentic leadership dedicated to nursing, which would consider rationing nursing care (Fast & Rankin, ) and patient safety (Agnew et al., ; Dirik & Seren Intepeler, ; Perry, ; Stewart & Usher, ). Such a model can be important for in improving the curricula of pre‐ and postgraduate courses.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, it has been stressed in the literature that effective leadership in nursing is among crucial elements contributing to the proper functioning of healthcare systems guaranteeing patients’ safety (McCay, Lyles, & Larkey, ; Smith & Johnson, ) . Effective leadership can directly contribute to a positive change in the nurses’ behaviour in everyday clinical work: increasing the effectiveness of interdisciplinary teams, reducing the number of medical errors, increasing the safety of patients and medical staff and—consequently—improve medical services (Agnew, Flin, & Reid, ; Dirik & Seren Intepeler, ; Stewart & Usher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, I am writing in relation to the article 'The influence of authentic leadership on safety climate in nursing' (Dirik & Intepeler, 2017). The study showed how authentic leadership affects safety climate by administering a survey with questions related to patient safety.…”
Section: The Influence Of Authentic Leadership On Safety Climate In Nmentioning
confidence: 99%
“…Reasoning and rationalism is another component identified in the present study. Reasoning and reasoning abilities are at the highest level after data processing (Dirik, Seren Intepeler, 2017). Professors who possess this attribute have received sufficient knowledge and are now given valuable experience in teaching.…”
Section: Resultsmentioning
confidence: 99%